FIH-1 engages novel binding partners to positively influence epithelial proliferation via p63 - Kaplan, Nihal (FASEB J, 2019)
Whereas much is known about the genes regulated by ΔNp63α in keratinocytes, how ΔNp63α is regulated is less clear. During studies with the hydroxylase, factor inhibiting hypoxia-inducible factor 1 (FIH-1), we observed increases in epidermal ΔNp63α expression along with proliferative capacity in a conditional FIH-1 transgenic mouse. Conversely, loss of FIH-1 in vivo and in vitro attenuated ΔNp63α expression. To elucidate the FIH-1/p63 relationship, BioID proteomics assays identified FIH-1 binding partners that had the potential to regulate p63 expression. FIH-1 interacts with two previously unknown partners, Plectin1 and STAT1 leading to the regulation of ΔNp63α expression. Two known interactors of FIH-1, ASPP2 and HDAC1 were also identified. Knockdown of ASPP2 upregulated ΔNp63α and reversed the decrease of ΔNp63α by FIH-1 depletion. Additionally, FIH-1 regulates GADD45α, a negative regulator of ΔNp63α by interacting with HDAC1. GADD45α knock down rescued reduction in ΔNp63α by FIH-1 depletion. Collectively our data reveal that FIH-1 positively regulates ΔNp63α in keratinocytes via variety of signaling partners: (i) Plectin1/STAT1; (ii) ASPP2; and (iii) HDAC1/GADD45α signaling pathways.